Projeto Construindo Saberes e a formação para o exercício da docência: avaliação do Programa Prodocencia no âmbito da Universidade Federal do Tocantins - Souza, Jacqueline Ramos Macedo Antunes (2011)
The purpose of this research, which sometimes takes shape in this dissertation is to study and analyze the "Programa Consolidação das Licenciaturas - Prodocência", under the policy of education and more specifically the project "Construindo Saberes: o ensino por projetos nas licenciaturas”**, institutional proposal of the Federal University of Tocantins – UFT, financed with resources from Prodocência, aiming to improve the training in undergraduate programs in public universities. The University is inserted and is determined by economic, political and cultural interests defined by the dichotomy of the social force’s play. In this analytic line, I’ve assumed that the public University still is the major locus for training of professionals, considering its dimensions of social institution and of public nature. I approach especially the public university as a space for training, considering his proposal to train teachers in their undergraduate programs in order to meet the demands of a democratic state, young and lacking qualified professional to work in education: the state of Tocantins. We decided, me and my advisor, as a method the historical-critical dialect, seeking to explain social transformations based on a historical analysis of society and their method of permanent movement, and also with a more qualitative than quantitative of the available materials research (theory and research), properly systematized, following the methodology of content analysis. The result of empirical research conducted with a group of teachers and students participating in the project “Construindo Saberes: o ensino por projetos nas licenciaturas”* reveals that the Prodocência fulfills its function in a scenario where there was not, so far, a specific program for teaching incentive by funding agencies associated with the Ministry of Education. However, by the discourse of the subjects involved, we clearly see that the project's actions underscored the importance of more research than the act of teaching itself.